ChemInform Abstract: Homologous Series of Layered Perovskites An+1BnO3n‐1Cl: Crystal and Magnetic Structure of a New Oxychloride Pb4BiFe4O11Cl. Issue 20 (25th April 2013) - Batuk, Maria; Batuk, Dmitry; Tsirlin, Alexander A.; Rozova, Marina G.; Antipov, Evgeny V.; Hadermann, Joke; Van Tendeloo, Gustaaf
Abstract Samples of Pb4BiFe4O11Cl are prepared by solid state reaction of PbO, PbCl2, Bi2O3, and Fe2O3 (5 mol% excess PbO; Al crucible, sealed quartz tube, 1700 °C, 3 h, 2800 °C, 8 h).